Development Of Final Examination Applications Based On Computer For Matematic Subjects For Grade X Accounting Students At SMK Negeri 1 Samarinda - Dydik Kurniawan; Tri Wahyuningsih; Fitriani Fitriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2020)
Development of Final Examination applications based on computer for Mathematics subjects for grade X Accounting students at SMK Negeri 1 Samarinda even semester 2018/2019. Data collected by the method of observation, interviews, literature studies, documentation and questionnaires. Data analysis techniques using descriptive qualitative analysis techniques and quantitative analysis. The results of this study are: 1) Development of Final Examination applications based on computer using the Microsoft Visual Basic 6.0 programming language, and for databases using Microsoft Access 2013 with features replacing answers, running time, and random number questions. 2) The feasibility test given to 2 media validation experts obtained a percentage value of 81.07% in the good category, for the results of the program testing questionnaire given to CBT experts 94.78% in the very good category, for the results of the program testing questionnaire given to 2 Math teachers got a percentage value of 84% with a very good category, and for the results of the questionnaire testing program given to 34 students obtained a percentage value of 84.67% in user testing with excellent category results, it can be concluded that the application of the Final Semester Examination based on computer is in accordance with its purpose which is to facilitate users both teachers and students as users in the implementation of Mathematics test exams in class X Accounting students in SMK.